Caracterização hidrodinâmica e estimativa do transporte de sal no estuário do rio São Francisco - AL/SE - Souza, Rodolfo Marcelo Gonçalves (2015)
The São Francisco River is extremely important at national and regional levels due to its multipurpose water resources. The São Francisco estuary plays an important role on both ecological and socio-economic aspects at local scale. The estuary is located at the border of the states of Sergipe and Alagoas, in the Lower São Francisco section, between the coordinates 10º25 'S and 36º23' W. This study aims to characterize the circulation and salt transport, and saline intrusion during in the São Francisco river estuary. Analysis of thermohaline properties and currents sampled at an anchor station in the estuary main channel was made in terms of two consecutive spring-neap tidal cycles in the summer season. A side mounted ADCP was utilized to measure vertical current profiles and was augmented with conductivity-temperature-depth (CTD) casts from surface to bottom every 30 min, and wind conditions were measured by a weather station. Along-channel stations were also occupied during spring and neap high slack water to estimate the upstream saline water incursion along the river channel. Saline waters penetrated further upstream during the neap high slack water reaching ~ 8.0 km, compared to ~ 6.8 km in the spring high slack water. Such low excursion in salinity water was associated with high tidal current generated by southeast winds, which reduced the downstream river water strength pushing the salt water toward the estuary upper reaches. These results, associated with the high water column vertical stability (RiL >20) revealed that the driving mechanism for the estuary circulation and mixing was mainly balanced by the fresh water discharge and the tidal forcing associated with the gravitational circulation. The increase in the up-estuary residual currents during the neap tide conditions was result of strong winds, and indicates the tendency of salt transport towards a balance in the neap tide.